'Meyer-Neldel Rule': True History of its Development and its Intimate Connection to Classical Thermodynamics - Starikov, E.B. (Journal of Applied Solution Chemistry and Modeling, 2014)
The history of the Meyer-Neldel rule's development and the initial collective efforts toward its comprehension have been described here. The whole story gives a nice occasion to trigger thorough analysis of the basic thermodynamic laws and looking for the true sense of the entropy notion.